Developing Web-Based Interactive Learning Media: Improving Student Engagement in Natural and Social Sciences at Madrasah Ibtidaiyah - Ulfatun Nadhiroh; Nur Cholid; Fitria Martanti; Nurul Asima (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The urgency of developing web-based interactive media wordwalls is urgently needed to provide interactive, contextual learning according to the needs of students in the digital era. The purpose of this study is to analyze the needs for the development of Natural and Social Sciences learning media and to assess the feasibility of the developed media. This type of research is R&D (Research and Development). The object of research in this study is the web-based interactive learning media Wordwall in the science subject of class IV, which is examined from the aspects of feasibility, validity, practicality, and effectiveness of its use in improving the quality of learning. The research subjects in this study are teachers and grade IV students at Madrasah Ibtidaiyah Negeri Semarang City, who are involved in the stage of needs analysis, limited trials, and response to the use of media. The procedure in this research and development applies the Sugiyono development model procedure, which is only carried out until the sixth stage. Data collection was carried out by conducting observations, interviews, questionnaires and documentation. The data analysis technique in this study uses qualitative and quantitative descriptive analysis techniques through questionnaires of the needs of educators, students, media experts and material experts. The results of the study show that the Wordwall-Based Interactive Learning media for Natural and Social Sciences Class IV Madrasah Ibtidaiyah Negeri Semarang City is very valid to be tested on students. The validation results from media experts obtained a score of 50, an average score of 5.0, and a validity of 100%. Meanwhile, the subject matter experts obtained a score of 48, an average score of 4.8, and a validity of 96%. The results of the analysis showed that the interactive media based on the web word wall of the Natural and Social Sciences subject was very valid.